A blueberry MIR156a–SPL12 module coordinates the accumulation of chlorophylls and anthocyanins during fruit ripening. (20th July 2020) - Li, Xuyan; Hou, Yanming; Xie, Xin; Li, Hongxue; Li, Xiaodong; Zhu, Yan; Zhai, Lulu; Zhang, Chunyu; Bian, Shaomin
Abstract : A MIR156 – SPL regulatory module ( VcMIR156a – VcSPL12 ) was identified in blueberry and is involved in the regulation of fruit coloration, likely through mediating the accumulation of both chlorophylls and anthocyanins. Abstract: Color change is an important event during fruit maturation in blueberry, usually depending on chlorophyll degradation and anthocyanin accumulation. MicroRNA156 (miR156)– SPL modules are an important group of regulatory hubs involved in the regulation of anthocyanin biosynthesis. However, little is known regarding their roles in blueberry or in chlorophyll metabolism during color change. In this study, a MIR156 gene ( VcMIR156a ) was experimentally identified in blueberry ( Vaccinium corymbosum ). Overexpression of VcMIR156a in tomato ( Solanum lycopersicum ) enhanced anthocyanin biosynthesis and chlorophyll degradation in the stem by altering pigment-associated gene expression. Further investigation indicated that the VcSPL12 transcript could be targeted by miR156, and showed the reverse accumulation patterns during blueberry fruit development and maturation. Noticeably, VcSPL12 was highly expressed at green fruit stages, while VcMIR156a transcripts mainly accumulated at the white fruit stage when expression of VcSPL12 was dramatically decreased, implying that VcMIR156a – VcSPL12 is a key regulatory hub during fruit coloration. Moreover, VcSPL12 decreased the expression of several anthocyanin biosynthetic and regulatory genes, and a yeast two-hybrid assay indicated that VcSPL12 interacted with VcMYBPA1. Intriguingly, expression of VcSPL12 significantly enhanced chlorophyll accumulation and altered the expression of several chlorophyll-associated genes. Additionally, the chloroplast ultrastructure was altered by the expression of VcMIR156a and VcSPL12 . These findings provide a novel insight into the functional roles of miR156– SPLs in plants, especially in blueberry fruit coloration.